Beneficial rhizobacteria and cover crops on soybean development - Natasha Ohanny da Costa Monteiro; Adriano Stephan Nascente; Nara Oliveira Silva Souza; Dennis Ricardo Cabral Cruz; Izabely Vitória Lucas Ferreira; Izaque de Sousa Rocha (Revista Ceres)
ABSTRACT Soybean cultivation holds national and international significance, necessitating sustainable production practices. This study evaluated the impact of plant growth-promoting rhizobacteria (PGPR) and cover crops on soybean yield components and grain yield. The experiment followed a randomized block design in a 5 × 2 factorial scheme with four replications. Treatments included the application of a PGPR combination (Bacillus sp. + Serratia marcescens) and five cover crops grown in the off-season: rice, corn, millet, Urochloa ruziziensis, and a cover crops mix. Over five agricultural seasons (2019/20–2023/24), we assessed the number of pods per plant, grains per pod, 100-grain mass, and grain yield. Cover crops did not influence yield components or grain yield. However, applying the PGPR mixture (Bacillus sp. BRM 63573 + Serratia marcescens BRM 32114) significantly improved 100-grain mass and grain yield. Among climatic factors, solar radiation was the primary determinant of grain yield variation. These findings highlight the potential of PGPR to enhance soybean production sustainably, while cover crops may require further investigation to optimize their role in this system.